Impact of Fathonah Transparency on Educational Financing Access - Rofiqoh, Lela; Lusianti, Dina; Widodo, Widodo; Khajar, Ibnu; Mutamimah, Mutamimah; Yusoff, Rushami (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The fundamental problem in the management of educational institutions in Indonesia lies in the limited access to financing, caused by weak transparency, unequal distribution of funds, and poor accountability, which creates a research gap concerning the effectiveness of transparency in enhancing trust in financial institutions. This study introduces the concept of Fathonah Transparency, a synthesis of sound corporate governance principles with intellectual, spiritual, and Islamic ethical intelligence, which is expected to strengthen the reputation of educational institutions and significantly improve their access to external financing sources. The research involved 350 academic institutions in Central Java selected through purposive sampling. Data analysis employed the Partial Least Squares–Structural Equation Modelling approach to examine causal relationships among variables, particularly the dimensions of acceptable transparency, relevant content, and accountability. The findings reveal that all three dimensions significantly influence reputation and access to financing, with reputation serving as a strong mediating factor that reinforces the link between transparency and funding opportunities. The discussion emphasises that intelligent, relevant, and accountable transparency grounded in Islamic values not only enhances the social legitimacy of educational institutions but also fosters greater trust among financial providers, thereby contributing theoretically to the development of Islamic value-based governance and offering practical implications for strengthening the financing system in Indonesian education.